The time-course of voluntary and electrically evoked muscle performance during and after stretch-shortening exercise is different - Skurvydas, A.; Mamkus, G.; Dudonien, V.; Kamandulis, S.; Mickeviciene, D.; Masiulis, N.; Stanislovaitis, A.; Streckis, V. (Journal of Sports Science & Medicine, 2007)
The aim of the study was to establish the dynamics of maximal voluntary contraction force (MVCF), height of drop jump (DJ) and electrically evoked quadriceps muscle force at different stimulation frequencies during and after 100 DJs (stretch-shortening exercise, SSE). Healthy untrained men (n = 11; age = 21.8 ± 1.7 years) participated in the study. DJs were performed with 30 s intervals between jumps from the height of 0.5 m with counter-movement to 90 degrees angle in the knee and immediate maximal rebound. The force of the quadriceps muscle, evoked by electrical stimulation at 1 Hz (Pt), 20 Hz (P20) and 100 Hz (P100) frequencies (electrically evoked performance, EEP), MVCF and height of DJ (voluntary evoked performance, VEP) were established during SSE (after 10, 50, 100 DJ) as well as at 1, 4, 8, 24, 48 and 72 h after SSE. Time-course of P20 and P100 during and after SSE was time (ANOVA: p < 0.001) and frequency dependent (ANOVA: p < 0.001) The Pt, P20 and P100 decreased significantly (p < 0.01) more than MVCF and H of DJ during SSE. At the beginning of SSE (during 1-10 DJs) P20 and P100 decreased significantly (p < 0.001) more than during 11-50 and 51-100 DJs. There was a significant (p < 0.05) increase in Pt, P20 and P100 from 8 h to 48 h, whereas height of DJ and MVCF significantly decreased at that time. In conclusion, the differences in time course of VEP and EEP are most evident at beginning of SSE, where VEP does not change as EEP decreases, and within 8-48 hours after SSE, where VEP decreases as EEP increases.